Comparison of laparoscopic Heller myotomy and endoscopic balloon dilation in the treatment of achalasia: Effects on quality of life and patient satisfaction - ATALAY S.; AKÇAKAYA A. (My University, 2024)
BACKGROUND: Achalasia is a rare neurodegenerative disease of the esophagus that causes impaired esophageal peristalsis and the inability of the lower esophageal sphincter (LES) to relax. This results in symptoms such as dysphagia, regurgitation, chest pain, and weight loss. Among the treatment options, Laparoscopic Heller Myotomy (LHM), Endoscopic Balloon Dilation (EBD), and Peroral Endoscopic Myotomy (POEM) are commonly used methods. The aim of this study was to compare the efficacy and clinical long-term results of LHM and EBD in treating achalasia. METHODS: Patient records from Bezmialem Vak & imath;f University Hospital were reviewed, and 36 patients diagnosed with achalasia who underwent LHM and EBD were included in the study. Patients were evaluated using the Pre-operative Eckardt Score (Pre-ES) for preoperative evaluation, the Post-operative Eckardt Score (Post-ES) for postoperative evaluation, the Achalasia Specific Quality of Life (ASQL) questionnaire, and the Patient Satisfaction Scoring (PSS). RESULTS: The mean age of the 19 patients who underwent LHM was 49.37 +/- 10.48 years. The mean age of the 17 patients who underwent EBD was 59.24 +/- 14.39 years. Perioperative complications included esophageal mucosal perforation in one patient in the LHM group, bleeding in three patients (17.64%), and esophageal perforation in one patient (5.88%) in the EBD group. At a mean follow-up of 90 months, gastroesophageal reflux developed in two patients (10.53%) in the LHM group and eight patients (47%) in the EBD group. The Pre-ES was similar in both groups. The Post-ES significantly decreased in the LHM group compared to the EBD group. When ASQL and PSS results were analyzed between the LHM and EBD groups, it was concluded that LHM was more effective than EBD in improving the quality of life and providing patient satisfaction (p-value: 0.001). CONCLUSION: In light of these findings, it was concluded that LHM is a safer intervention compared to EBD and should be prioritized, considering the low risk of complications, improved quality of life, and high level of satisfaction.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Health Sciences; Klinik Tıp; Klinik Tıp (Med); Clinical Medicine; Clinical Medicine (Med); Acil Tıp Hizmetleri; Emergency Medical Services